2019
DOI: 10.3389/fneur.2019.01046
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Cross-Sectional Study to Investigate the Biomarker Potential of Phosphorylated Neurofilament-H and Immune Mediators of Disability in Patients With 5 Year Relapsing-Remitting Multiple Sclerosis

Abstract: Objective: To test the feasibility of conducting a full-scale project evaluating the potential value of the phosphorylated neurofilament H (pNF-H) and several cytokines as disability markers in relapsing-remitting multiple sclerosis (RRMS).Methods: Twenty-four patients with 5-year RRMS evolution and eleven healthy control subjects entered the study. None of the participants had an inflammatory systemic or metabolic disease. Disability progression was evaluated using the Expanded Disability Status Scale. Serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Herrera et al also showed increased NF-H concentrations in patients with 5 year RRMS evolution. In their study, a correlation between NF-H levels and disease progression was observed, which suggested its potential reliability in monitoring the clinical condition of RRMS patients [39]. Shehab et al obtained similar results.…”
Section: Heavy Neurofilament (Nf-h)mentioning
confidence: 67%
“…Herrera et al also showed increased NF-H concentrations in patients with 5 year RRMS evolution. In their study, a correlation between NF-H levels and disease progression was observed, which suggested its potential reliability in monitoring the clinical condition of RRMS patients [39]. Shehab et al obtained similar results.…”
Section: Heavy Neurofilament (Nf-h)mentioning
confidence: 67%
“…Interestingly, despite a higher increase observed in CSF NfH than in NfL levels during disease activity NfL still proved to be a more reliable marker for disease stability 340 . Higher NfH levels were also associated with relapse activity 340,358 , EDSS 359 and MSSS 360 scores and T2 lesion volume 360 . These findings are refuted by other studies which failed to demonstrate a correlation between NfH levels and clinical and MRI variables of MS patients 315,324 .…”
Section: Neurofilament Heavy Chain In Msmentioning
confidence: 98%
“…The neurofilament heavy chain (NfH) is an essential component of the neuronal cytoskeleton. It is highly expressed in large-caliber axons, playing a critical role in maintaining the axonal structural integrity, and can be used to indicate the extent of neuro-axonal damage ( Petzold et al, 2016 ; Herrera et al, 2019 ). NfH levels in the CSF were related to the clinical severity of MS and neurodegeneration in MRI ( Khalil et al, 2013 ; Petzold et al, 2016 ).…”
Section: Potential Biochemical Neurodegeneration Markers Associated W...mentioning
confidence: 99%